Six-Month Outcomes After High-Risk Coronary Artery Bypass Graft Surgery and Preoperative Intra-aortic Balloon Counterpulsation Use: An Inception Cohort Study - Litton, E.; Bass, F.; Delaney, A.; Hillis, G.; Marasco, S.; McGuinness, S.; Myles, P.; Reid, Christopher; Smith, J. (WB Saunders, 2018)
Objective: To inform the design of a pivotal randomized controlled trial of prophylactic intra-aortic balloon counterpulsation (IABC) in patients undergoing coronary artery bypass graft (CABG) at high risk of postoperative low cardiac output syndrome (LCOS). Design: Inception cohort study. Setting: A total of 13 established cardiac centers in Australia, Canada, New Zealand, and the United Kingdom. Participants: Adult patients were eligible for inclusion if they were listed for CABG surgery and had 2 or more LCOS risk factors (low ejection fraction, severe left main coronary artery disease, redo sternotomy, unstable angina). Interventions: Outcomes of interest were a composite outcome of in-hospital mortality, postoperative acute myocardial infarction (AMI), acute kidney injury (AKI), or stroke as well as 6-month vital status and quality of life using the EuroQol 5-dimensional questionnaire (EQ5D). Measurements and Main Results: The study included 136 participants over a 29-month period. Overall, in-hospital and 6-month mortality occurred in 7 (5%) and 11 (8%) participants, respectively. The composite outcome occurred in 60 (44%). The mean increase in EQ5D summary index at 6 mont hs was 0.10 (standard deviation 0.24, p = 0.01). Perioperative AMI, AKI, or stroke significantly decreased the odds of a clinically meaningful improvement in quality of life (odds ratio 0.32; 95% confidence interval 0.13-0.79; p = 0.014). Preoperative IABC was used in 39 participants and did not predict postoperative outcomes. Conclusions: The study identified a group of patients at risk of LCOS in whom CABG surgery was associated with a substantial burden of perioperative morbidity. Preoperative IABC use was variable, supporting the need for further research.